Atomic-scale unveiling of multiphase evolution during hydrated Zn-ion insertion in vanadium oxide - Pilgyu Byeon (Nature Portfolio, 2021)
The detailed understanding of the structural variations during cycling in cathodes for Zn-ion aqueous rechargeable batteries is still limited. Here, the authors utilize atomic-column-resolved scanning transmission electron microscopy to elucidate multiphase evolution during hydrated Zn-Ion insertion in vanadium oxide.